Transcriptome and anatomical analysis of Stipa breviflora in response to different grazing intensities in desert steppe - Wang, Xiaoyu; Wu, Jierui; Dai, Rui; Zhang, Zhiqiang; Wang, Yunbo; Mi, Fugui (Frontiers in Plant Science, 2024)
Stipa breviflora is a dominant species in the desert steppe of northern China. Grazing is the main land use pattern of grassland, which could cause a variety of adaptive evolutionary mechanisms in plant community composition as well as individual plant growth and morphological characteristics. However, very little is known about the morphological structure and transcriptional regulation response to different grazing intensity in S. breviflora. In this study, transcriptome, and anatomical analysis of S. breviflora under different grazing intensities, including no grazing (CK), moderate grazing (MG) and heavy grazing (HG), were performed. The anatomical analysis results showed that epidermis cells and xylems significantly thicken with grazing intensity, suggesting that grazing results in increasing lignification. Furthermore, the composition of cell wall such as lignin, cellulose, hemicellulose, and pectin were all increased dramatically and significantly under both the moderate and heavy grazing. Transcriptome analysis showed that the differential expressed genes related to different grazing intensities were also engaged in plant cell walls formation and photosynthesis and respiration. In addition, activities of ATP synthase and Rubisco activating enzyme (RCA) increased significantly with enhanced grazing intensity and differed significantly between moderate and heavy grazing intensities. Trends in transcriptome and plant phenotype changes are consistent. Taken together, these results indicated that S. breviflora has evolved a grazing tolerance strategy under long-term grazing conditions, influencing photosynthesis and respiration in terms of its own structure and enzyme activities in the body, to maintain normal life activities under different grazing conditions.